HMGB1 protein as a novel target for cancer. (2019) - Tripathi, Alok; Shrinet, Kriti; Kumar, Arvind
Abstract: Highly conserved nuclear protein High Mobility Group Box1 (HMGB1) present in mammals has functionality as an immuno-modulator in the form of cytokine molecule, as a nuclear factor to regulate these molecules and DNA structural determination. It has proximal homologous DNA binding domains Box-A, Box-B and distal C-terminal domain. Reduced form exists in basic condition has chemotaxis activity, while form with disulphide bond reduced at 106 th cysteine showed cytokine activity. The oxidized form is devoid of both activities. HMGB1 binds and bends dsDNA and also activates genes for secretion of inflammatory cytokines such as IL-1β, TNF-α, IL-6 and IL-18. It can interact with transcription factors Rel/NF-κB and p53 responsible for up-regulating oncogenes. Oxidative stressed injured tissues actively secrete HMGB1 outside cells to necrotize other nearby tissues passively in cytosol. Acetylation of HMGB1 weakens its binding with DNA, and promotes its migration to different tissues leading to secretion of inflammatory-cytokines. HMGB1 expression has been found very important in the genesis and promotion of different cancer by promoting metastasis. In current article, we emphasized on condition based structural variability of HMGB1, mechanism of release, physiological functions and its functionality as a biomarker for cancer to be targeted to curb cancer genesis and progression.